Unique molecular profile of exosomes derived from primary human proximal tubular epithelial cells under diseased conditions. Issue 1 (1st December 2017) - Wang, Xiangju; Wilkinson, Ray; Kildey, Katrina; Potriquet, Jeremy; Mulvenna, Jason; Lobb, Richard J.; Möller, Andreas; Cloonan, Nicole; Mukhopadhyay, Pamela; Kassianos, Andrew J.; Healy, Helen
ABSTRACT: Human proximal tubular epithelial cells (PTEC) of the kidney are known to respond to and mediate the disease process in a wide range of kidney diseases, yet their exosomal production and exosome molecular cargo remain a mystery. Here we investigate, for the first time, the production and molecular content of exosomes derived from primary human PTEC cultured under normal and diseased conditions representing a spectrum of in vivo disease severity from early inflammation, experienced in multiple initial kidney disease states, through to hypoxia, frequently seen in late stage chronic kidney disease (CKD) due to fibrosis and vascular compromise. We demonstrate a rapid reproducible methodology for the purification of PTEC‐derived exosomes, identify increased numbers of exosomes from disease‐state cultures and identify differential expression levels of both known and unique miRNA and protein species from exosomes derived from different disease‐culture conditions. The validity of our approach is supported by the identification of miRNA, proteins and pathways with known CKD associations, providing a rationale to further evaluate these novel and known pathways as targets for therapeutic intervention.